Rehabilitation Program in a Patient Undergoing Mitral and Aortic Valve Replacement Surgery - Purwati Pole Rio; Muhamad Taufik Ismail; Irsad Andi Arso (ACI (Acta Cardiologia Indonesiana), 2017)
Heart disease due to valvular anomaly has increased prevalence along with increasing age. The operative management including reparation or substitution with prosthetic valve is the main therapy. Still becoming question mark either rehabilitation program is benefcience for patient undergoing valvular surgery. We report a patient with heart failure due to valvular heart disease and underwent double valve replacement surgery. Cardiac rehabilitation phase 1 and phase 2 was done. Patient feel physical condition is much better than before.